PEMBUKTIAN TERBALIK DALAM TINDAK PIDANA KORUPSI - H. Firman Freaddy Busroh (to-ra, 2016)
No. 24 Prp of 1960 on Investigation, Prosecution and Investigation of Corruption. Furthermore, in 1971 formed the Law No. 3 of 1971 on the Eradication of Corruption and then Law No. 31 of 1999 on Corruption Eradication embracing sistem of proof is limited as stipulated in Article 37, which allows a reverse authentication is limited to a particular property and the confiscation of proceeds of corruption. Both Law, both Law No. 3 of 1971 and Law No. 31, 1999, in principle, still use the theory of negative evidence. While in Law No. 20 of 2001 on Corruption Eradication, adheres Sistem and Balanced Reversal of the Burden of Proof, which is provided for in Article 12 B, 12 C, 37, 37A, 38 A and 38 B. However, these rules have not been implemented to date in an attempt the eradication of corruption in Indonesia.The urgency of proof in the eradication of corruption First, restore the state financial losses made by the perpetrators of corruption, second, eradication of corruption is not only relying on law enforcement action is repressive, but also depends on preventive measures as a cease- desist follow corruption, and Third, improve the bad image of Indonesia are classified as high-level corruption, where one of the causes is the growing corruption committed by state officials. Reversed burden of proof required for a person attached to her duties as official organizer of the state, not him as a personal (individual). Proving wealth of local heads of government have to do with the approach of the Law of Administration and administrative sanctions and criminal law approach through the Corruption Court. Proof of the origin of the assets Servants and State Officers carried out by effecting a state administrative law and administrative law sanctions. If you find any indication of the wealth of the proceeds of corruption and has been demonstrated in reverse by Servants and State Officers that that wealth came not from corruption, then followed up through the procedures of criminal law and subject to criminal sanctions through Crime Court Corruption.Kata kunci: Pembuktian Terbalik